ChemInform Abstract: Antimonato Polyoxovanadate Based Three‐Dimensional Framework Exhibiting Ferromagnetic Exchange Interactions: Synthesis, Structural Characterization, and Magnetic Investigation of {[Fe(C6H14N2)2]3 [V15Sb6O42(H2O)] }·8H2O. Issue 22 (13th May 2013) - Wutkowski, Adam; Naether, Christian; Koegerler, Paul; Bensch, W.
Abstract Dark red needles of [Fe(H2dach)2]3 [V15Sb6O42(H2O)] ·8H2O (I) are obtained under solvothermal conditions form a mixture of FeSO4, NH4VO3, Sb2O3, H2O, and trans‐1, 2‐diaminocyclohexane (dach), the latter acting as ligand, solvent, and reducing agent (sealed glass tube, 160 °C, 7 d).